The Effectiveness of Reading Activity To Improve Vocabulary Mastery of The Eight Grade Students of SMP Negeri I Madapanga-Bima - Suratman (STKIP Taman Siswa Bima, 2018)
The objectives of this research are to describe the effectiveness of reading activity to improve vocabulary mastery of the eight grade students of SMP Negeri I Madapangga-Bima and to find out whether there is a significant difference between the vocabulary mastery of the students who are taught through reading activity and the students who are taught without reading activity. This research was an experimental research study that was held in SMP Negeri I Madapangga. The research subject was the eighth grade students in the academic year of 2017/2018. The number of students was 214. The experimental research involved one experimental group compared with the control group. Class B belongs to the experimental group taught through reading activity and class A belongs to the control group taught without reading activity. Both classes were given a pre-test at the beginning. The post-test were given at the end of the meeting. For collecting the data the researcher applied multiple choice test and the data were analyzed by applying t-test computation, descriptive and inferential analysis. The research findings indicate that the mean score of the experimental group is 23.08, and the mean score of the control group is 19.94. It means that the hypothesis alternative (ha) is accepted. It can be said that there is a significant difference in vocabulary mastery between the students who are taught through reading activity and the students who are taught without reading activity. The result of t-test shows that t-observed value is higher than t-value of the table (3.928 > 1.990)at the significance level of 5 %. In conclusion, improving the students’ vocabulary mastery through reading activity is more effective than improving the students’ vocabulary mastery without reading activity.